Prevention of Adiposity by the Oral Administration of β-Cryptoxanthin - Takayanagi, Katsuhiko (Frontiers in Neurology, 2011)
β-Cryptoxanthin (β-CRX) is a carotenoid found in human blood. It is specifically rich in Satsuma mandarin (Citrus unshiu Marc.) but very little in other fruits or vegetables. Several reports indicate the health promoting benefits of β-CRX. As we had reported visceral fat reduction on mildly obese male by the oral administration of β-CRX, a detailed mechanism has not been identified. To identify the mechanism, obese model mouse, TSOD was used in the present study. Oral administration of β-CRX repressed body weight, abdominal adipose tissue weight and serum lipid concentrations on TSOD mice. The outstanding observation is the significant repression of adipocyte hypertrophy. DNA micro array analysis strongly indicates that the oral administration of β-CRX represses the inflammatory cytokine secretion and improves the lipid metabolism and the energy consumption. It also suggests these effects are partly mediated by PPAR-α, not only lipid metabolism and adipocyte differentiation control but possibly internal circadian clock modulation.